Mediation as a value and chance for Ukraine - Patsurkivskyy, Petr; Havrylyuk, Ruslana (Університет «КРОК», 2021)
In the article mediation as a qualitatively isolated self-sufficient value (culture) of a developed civil society is investigated from the standpoint of anthroposociocultural approach. It is substantiated that the quintessence of mediation is the preservation and protection of human dignity in resolving conflicts by their participants with the assistance of professional medi- ators, as well as revealed the basic principles of mediation – human-centrism, denial of violent orders in society and paternalism. It is proved that mediation has a complex nature – it is dialogical, it exists as both a public good and a social service, it is a form of freedom, justice and social partnership, and the attributes of mediation are the trust of the conflicting parties to each other and social optimism. It is substantiated conclusions that: a) the assertion of mediation as a value (culture of mediation) in society is a real Copernican revolution in public views on methods of conflict resolution and one of the most important manifestations of the subjectivity of the individual; b) mediation belongs to paradigmatically opposite values in comparison with the values of state ju- diciary; c) mediation embodies the postmodern way of being and thinking, and therefore can be adequately perceived through the corresponding categorical-conceptual apparatus of non-classical standards of science, from the worldview and methodological approaches of postmodernism.
Keywords: mediation; judiciary; value; value matrix of mediation; value matrix of judiciary; anthroposociocultural code of mediation; sociocultural code of judiciary